Modification of the Kato-Katz Diagnosis Technique Using “Canang” Flower Waste Extract as a Staining for Ascaris lumbricoides Eggs - Maheswari, Kadek Indira; Janendra, Putu Sathiya Adi; Widnyana, I Komang Tri Yasa; Mahayana, Dewa Gede Putra; Pramesti, Komang Kirana Ardhia; Dwisaputra, Indra; Permasutha, Made Bayu; Wiguna, Nyoman Intan Permatahati; Giri, Made Kurnia Widiastuti (HAYATI Journal of Biosciences, 2026)
Helminthiasis, particularly that caused by Ascaris lumbricoides, is a major global health issue, especially in areas with poor sanitation. One method for preventing and controlling Ascaris lumbricoides infection is through identification via the Kato-Katz diagnostic technique. The use of synthetic dyes, such as methylene blue, in the Kato-Katz method raises concerns for both human health and the environment. In humans, methylene blue causes skin irritation, gastrointestinal issues upon ingestion, and systemic effects. Furthermore, its environmental impact includes reducing light penetration and acting as a toxic component in food chains. An alternative approach involves utilizing post-use offerings from Hindu rituals in Bali, known as canang, which consist of flower components such as Impatiens balsamina L. and Tagetes erecta. The natural dyes found in these flowers serve as an alternative to traditional staining methods. This study examined the efficacy of flower extracts as stainings using the cellophane absorption test, helminth egg detection and morphology identification, pH test, and measurement of heavy metal concentration. The dye made from canang flower waste at 3% did not differ much from manufactured stainings. Thus, canang flower waste is a safe alternative.